Cushing's syndrome in pregnancy: an overview - Vilar,Lucio (2007)
Cushing's syndrome (CS) during pregnancy is a rare condition with fewer than 150 cases reported in the literature. Adrenal adenomas were found to be the commonest cause, followed by Cushing's disease. The gestation dramatically affects the maternal hypothalamic-pituitary-adrenal axis, resulting in increased hepatic production of corticosteroid-binding globulin (CBG), increased levels of serum, salivary and urinary free cortisol, lack of suppression of cortisol levels after dexamethasone administration and placental production of CRH and ACTH. Moreover, a blunted response of ACTH and cortisol to exogenous CRH may also occur. Therefore, the diagnosis of CS during pregnancy is much more difficult. Misdiagnosis of CS is also common, as the syndrome may be easily confused with preeclampsia or gestational diabetes. Because CS during pregnancy is usually associated with severe maternal and fetal complications, its early diagnosis and treatment are critical. Surgery is the treatment of choice for CS in pregnancy, except perhaps in the late third trimester, with medical therapy being a second choice. There does not seem to be a rationale for supportive treatment alone.